Impact of Carbon Credits as Revenue Enhancers in Blended Adaptation Finance for Nature-based Resilience Solutions Across Emerging Economies - Rao, U.L. Narasimha (CSID Journal of Infrastructure Development, 2026)
Emerging economies face an annual adaptation finance gap of $300–$500 billion. Nature-based resilience solutions (NbRS) such as mangroves and agroforestry remain critically underfunded despite their cost-effective climate benefits. Carbon credits have been examined mainly in mitigation contexts; their role as revenue enhancers in blended adaptation finance for NbRS is untested. This study had three objectives: quantifying revenue uplift from credits, evaluating how certification reduces investor risk, and forecasting scalability under different blend ratios. A qualitative comparative case study was applied to 12 NbRS projects across emerging economies. Eight cases were from India; the rest came from Kenya and Indonesia. Data came from the Climate Policy Initiative, Verra, and Gold Standard. Carbon credits contributed 15–35% of total project revenues across the 12 cases. The average revenue uplift was 24%. Indian projects averaged 22%, compared with 18% in other cases. Verra and Gold Standard certification reduced investment risk in 75% of blended structures examined. Certified projects attracted private capital at 2.5 times the public contribution. The non-certified Coochbehar pilot recorded a 40% drop in investor participation due to verification gaps. Projects with Viability Gap Funding ratios of 25–35% scaled four times faster than higher-subsidy cases. If credits reach a 20% revenue norm across NbRS portfolios, annual mobilisation potential is projected at $50 billion. These findings position carbon credits as "resilience dividends" and extend blended finance theory beyond its mitigation focus. Policymakers and public sector professionals can use these findings to design credit-inclusive green bonds and attract private capital to NbRS. No prior study has empirically tested carbon credits as revenue enhancers in blended NbRS finance across countries or applied a revenue enhancement index to capture co-benefits beyond sequestration. Well-structured carbon credit mechanisms, backed by credible certification, can meaningfully close the adaptation finance gap in emerging economies.